Kepuasan Komunikasi Program Pengenalan Jurusan - Hilda Yunita Wono; Michelle Baby Natalie (Jurnal Komunikasi Global, 2019)
Continuing education to a higher level is an unavoidable need. A new student in a new place also needs to adapt well. Ciputra University takes part in assisting all students in adjusting to their academic life by arranging an orientation program, so they get to know their study program better. The orientation program is a yearly program organized by the Student Union so that it is important to see the communication satisfaction experienced by the participants and organizers. This research used a descriptive qualitative method by collecting data through in-depth interviews with six informants, three core committee members, and three of the most active participants. The results show that communication satisfaction is good. Things that need to be improved are the preparation time, time allocation to get feedback from participants, and appreciation for committee members.